Influência africana na arquitetura de terra de Minas Gerais - Juliana Prestes Ribeiro de Faria (2011)
The popular architecture is an important element of expression of the interactions observed between different cultures within a given society. The vast cultural diversity present in Brazil resulted in a great variety of architectonic (structural) legacies, including among these, the African inheritance. In this study, it is proposed the investigation of the African influence on the Brazilian architecture, which resulted from the interaction between the earth-construction techniques used by Western African slaves brought to work in Brazil and those used in constructions of the 18th century. The current investigation report us to the State of Minas Gerais, as the discovery of gold and precious stones facilitated the coexistence of different cultures which, immersed in a social dynamic without precedent, furnished the slaves with tools to stamp their houses with their distinct construction knowledge and practices. The autonomy given to these individuals during the conception of their houses in the farm, surrounding the village and in the houses settlement of the mining industry was different from that given to the slaves in the quilombos. This differentiation was reflected in the forms, use and appropriation of the spaces, although these were, in origin, always related to the African architectonic style. Thus, it was possible to confirm that the interactions between the spacial configuration and social structure observed in Western Africa and in the State of Minas Gerais are similar in many aspects and, in addition, these can be regarded as part of the Minas Gerais States cultural scenery.